ECONOMIC VIABILITY OF A NEW GAS- POWERED POWER STATION OR A NEW SOLID-FUEL POWER STATION ON THE SITE OF THERMO-PLANT TRBOVLJE - Kavkler, Alenka; Festiđ, Mejra (Journal of Energy Technology, 2024)
For an efficiency estimation of an investment in a gasͲsteam electric power station and a solid-fuel electric power station, we estimated the cost prices of electricity and two indicators of investment efficiency: internal rate of return and net present value. The risk of investment was estimated with sensitivity analysis. In this paper, we present three scenarios regarding the energy prices, fuel, the prices of emission coupons, capital costs and the selling price of electricity. For the first scenario, we used the present market values of relevant variables. According to these suppositions, we confirmed that an investment in a gasͲsteam power station is acceptable, but risky. In contrast, an investment in a solidͲfuel power station is not acceptable. Lower electricity prices are the main economic risk. The second scenario is based on theprojections of energy prices and prices of emission coupons according to the projection of the “Long run energy balance of RS for the period 2006Ͳ2026,” prepared by the Jožef Štefan Institute. Under these circumstances, both projects are acceptable. The third scenario is prepared according to the forecasts of the “Annual Energy Outlook 2009 – Early Release Overview.” Under these circumstances, both projects could be acceptable but risky.